PENERAPAN METODE SCRUM DAN VIRTUAL PRIVATE NETWORK DALAM PERANCANGAN SISTEM ORDERSALES - Tony Wijaya (CCIT Journal, 2018)
Sales Ordering System is a mobile application used by salesman to create sales invoice. With this system, salesman can directly input invoices to server computer at head office using their smartphones. It is possible because there is Virtual Private Network (VPN) that connect server PC with those smartphones. This system has featureof sales invoice which can be done using smartphone browser.The writer implements Scrum which is derived from Agile Methodology in this research to design the system.Scrum is a framework that focus at dividing main goal into several easy-to-achieve goals.Scrum assumed user requirements in a project development cannot be listed completely up front, because they often changed their minds in the process.Testing is done with blackbox method to ensure the feature mentioned above is well implemented.With sales ordering system, companies can achieve one step further in productivity and to give better service and satisfaction to consumer.